Isoflavone biochanin A, a novel nuclear factor erythroid 2‐related factor 2 (Nrf2)‐antioxidant response element activator, protects against oxidative damage in HepG2 cells. (27th May 2019) - Liang, Fuqiang; Cao, Weiwei; Huang, Yuting; Fang, Yajing; Cheng, Yuxin; Pan, Siyi; Xu, Xiaoyun
Abstract: Isoflavones are one group of the major flavonoids and possess multiple biological activities due to their antioxidant properties. However, a clear antioxidant mechanism of dietary isoflavones is still remained to be answered. In this study, the effects of isoflavones on the nuclear factor E2‐related factor 2 (Nrf2)–antioxidant response element (ARE) signaling pathway and the underlying molecular mechanisms were investigated. Results showed that isoflavones are potential Nrf2–ARE activators while their activities were structure dependent. Biochanin A (BCA), an O ‐methylated isoflavone with low direct antioxidant activity, can effectively protect HepG2 cells against tert ‐butyl hydroperoxide ( t ‐BHP)‐induced oxidative damage via activation of the Nrf2 signaling, and thereby the induction of downstream cytoprotective enzymes including NAD(P)H quinone oxidoreductase‐1, heme oxygenasae‐1, and glutamate‐cysteine ligase catalytic subunit. A molecular docking study revealed that BCA could directly bind into the pocket of Kelch‐like erythroid cell‐derived protein with CNC homology (ECH)‐associated protein 1 (Keap1), a cytoplasmic suppressor of Nrf2, to facilitate Nrf2 activation. The upstream mitogen‐activated protein kinase (MAPK) pathways were also involved in the activation of Nrf2 signaling. These findings indicate that the protective actions of dietary isoflavones against oxidative damage may be at least partly due to their ability to enhance the intracellular antioxidant response system by modulating the Nrf2−ARE signaling pathway.